Protein and amino acid composition ofwild caught freshwater crayfish (Pontastacus leptodactylus) in the reproductive season - Harlioglu, Ayse Gul; Yilmaz, Okkes; Erdogdu, Ayse; Siltar, Yesim Bulut (Soc Brasileira Carcinologia, 2021)
Interest in feeding crayfish under culture conditions has increased in the last few years; however, there is still a lack of information on feeding crayfish according to their nutritional requirements (i.e., protein and amino acid dietary demands of broodstock). In this study, the protein and amino acid composition of abdominal muscle, gonads and hepatopancreas of male and female broodstock crayfish Pontastacus leptodactylus (Eschscholtz, 1823) were determined in the reproductive season. The results show that in P. leptodactylus, the amount of protein in the ovary was 47.25 mg/g and that it was 35.03 mg/g and 39.36 mg/g in the testes and vasa deferentia, respectively. In males, the values of essential amino acids (EAA) obtained in the abdominal muscle were significantly lower than those obtained from the hepatopancreas, testes and vasa deferentia (P < 0.05). In female crayfish, EAA/total amino acids (TAA) were found to be 45.48 % in the ovary, which is significantly higher than that of the abdominal muscle (40.19 %) and hepatopancreas (42.14 %) (P < 0.05). The results also show that abdominal valine, threonine, lysine, and histidine were statistically higher in female crayfish than male crayfish (P < 0.01). Leucine was the major EAA found in males in abdominal muscle (8.73 %). In conclusion, this study analyzed the protein and amino acid composition of abdominal muscle, hepatopancreas and gonad of crayfish in the breeding season in order to understand the protein and amino acid contents of wild caught crayfish and get an idea on the nutritional requirements of P. leptodactylus in the reproductive season.
Keywords: Crustacean metabolism; gonad; hepatopancreas; protein composition